2004
DOI: 10.1109/tmag.2003.821155
|View full text |Cite
|
Sign up to set email alerts
|

Burnishing Heads In-Drive for Higher Density Recording

Abstract: We propose to establish flying clearance at the head-disk interface by wearing the slider region that contains the transducer. The wear process is controlled by slider design, disk design, and the techniques used to control contact pressure at the wear region. The resulting distribution of flying clearance for a population of head-disk interfaces provides performance gains associated with lower magnetic spacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…(In contact recording, the recording head needs to run in continuous contact with the disk for many years with negligible wear.) Recently, however, an initial burnishing phase has been proposed for removing the head overcoat and head recession as a way of achieving the very small spacing needed between the disk magnetic media and the read and write sensors in the head for 1 Terabit/in 2 recording densities [4,9,30], indicating the need to better understand and control the wear processes at contacting slider-disk interfaces.…”
Section: Insight Into Wear At Slider-disk Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…(In contact recording, the recording head needs to run in continuous contact with the disk for many years with negligible wear.) Recently, however, an initial burnishing phase has been proposed for removing the head overcoat and head recession as a way of achieving the very small spacing needed between the disk magnetic media and the read and write sensors in the head for 1 Terabit/in 2 recording densities [4,9,30], indicating the need to better understand and control the wear processes at contacting slider-disk interfaces.…”
Section: Insight Into Wear At Slider-disk Interfacesmentioning
confidence: 99%
“…Several techniques have been introduced to reduce the contact area of these low flying slider-disk interfaces in an effort to reduce friction: texturing air-bearing surface (ABS) [6][7][8], adding small contact pads on the slider surface [4,9], and texturing to the disk surface. While these techniques reduce friction substantially, further reduction is needed to ensure that occasional contacts do not have a detrimental impact on disk drive operations.…”
Section: Introductionmentioning
confidence: 99%
“…One post-slider fabrication process to reduce ABS was introduced by Strom et al (2004). The process is basically a burnishing technique to wear off the DLC coating of a slider's trailing pad that houses the read/write element, using the disk surface.…”
Section: Introductionmentioning
confidence: 99%
“…Khurshudov and Tyndall 3 and Khurshudov and Raman 4 defined and characterized the head-disk clearance and discussed the roughness effects on head-disk interface durability and reliability. In order to remove the excess thermal pole tip of heads and increase the head-disk clearance, media burnish capabilities have been investigated [5][6][7] . Kawakubo 8 studied the effect of tape-burnish on reducing asperity height by pin-on-disk tests and concluded that tape-burnish is good technique for reducing head wear and should be further studied to increase the asperity height-reduction efficiency while maintaining disk surface quality.…”
Section: Introductionmentioning
confidence: 99%